Isolation and chemical characteristics of rhamnose enriched polysaccharide from Grateloupia lithophila. (1st September 2018) - Seedevi, Palaniappan; Moovendhan, Meivelu; Sudharsan, Sadhasivam; Sivasankar, Palaniappan; Sivakumar, Loganathan; Vairamani, Shanmugam; Shanmugam, Annaian
Highlights: Polysaccharides was purified through Gel permeation chromatography. Polysaccharide contains high amount of carbohydrate. The molecular weight of purified polysaccharide was found to be 24 kDa. Rhamnose are found as major sugar. The structural characteristics of Rhamnose was studied by spectral techniques. Abstract: The crude polysaccharide was extracted from Grateloupia lithophila through hot-water extraction and deproteinization. Further, fractionated by anion-exchange column using Q-Sepharose and purified by gel-permeation chromatography using Sepharose 4-LB column. The crude and purified polysaccharide contains high carbohydrate (75.7 and 89.7%), ash (18.2 and 3.2%) and moisture (14.8 and 1.3%); the protein and uronic acid were absent. The molecular weight of crude, fractionated and purified polysaccharide was found to be 37 kDa, 29 kDa and 24 kDa. The monosaccharide composition of the crude polysaccharide was found to be having rhamnose (79.82%), fructose (8.38%), galactose (3.95%), xylose (3.31%) and glucose (1.48%); whereas the purified polysaccharide reported higher amount of rhamnose (95.88%), 1.13% of xylose and 2.21% of fructose. The structural elucidation of the purified polysaccharide was conformed as α-l -rhamnose through polarimetry, FT-IR and 1 H NMR spectroscopy.